Violence in Television Programs and Its Effect on Iraqi Youth (Journal of the College of Basic Education, 2022)
Abstract Due to the nature of television that deals with factual daily life of people، we notice that most channels started to deal with economical، political، and military conflict which spread all around the universe. Many of these programs focused on violence that exists between countries and internal conflicts. The subjects of violence now cover most news and drama programs، this spread to different and children programs. This did not limit to programs broadcasted by Arabic network channels but it moved to Iraqi network channels. The research was limited with the following question (Does television programs introduced by some Iraqi network channels contain large rate of violence?). The research is restricted to news، political، drama، and different programs from Iraqi network channels which are (Al-iraqia، Al-Sharqia، and Al-Baghdadia) and was restricted to programs being broadcasted in the period 1 / 1 / 2014 till 1 / 6 / 2014. The second chapter contained the theme of violence in television programs and a theme of violence in children and teenagers. The third chapter contained the procedures of the research. The method of this research was to analyze the data of the programs as sample of study. The research tool chooses (White) classification for evaluation and negative dominated values were chosen in television programs which are the value of violence and aggression opposite to positive social values which are respecting others، family bond، and social justice. After analyzing the sample of study the researchers reached to several conclusions:The focus of political، news، and drama programs was on violence and aggression that might lead to disobedience youth، especially teenagers.Most if research programs sample focused on aggression and disrespect of rules، and financial and administrative corruption especially in officials in the government.Review must be made in many of these programs and to choose ideas that contribute in bringing together national unity and everyone must bear the responsibilities in building the country in an appropriate way.